Natural forest disturbance and change in the Brazilian Amazon - Nelson, Bruce Walker (Remote Sensing Reviews, 1994)
Landsat Thematic Mapper images covering the entire 3.0 million km2 of forested Brazilian Amazon reveal natural change and disturbance occurring on a scale of decades to centuries. Natural and indigenous disturbances and synchronized phenologies are responsible for a dynamic spectral behavior in large portions of the Amazon Basin. -from Author
Keywords: Forest Disturbances; Tm Image; Amazon